Ojhung di Atas Bukit: Budaya Magis Orang Madura Utara - Raditya, Ardhie (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The lives of the people of North Madura have not been the focus of mainstream attention in the academic studies of Madura people. Most Madura researchers often look to the south because it is the center of urban progress on the island of Madura. The purpose of this research reveals the uniqueness of North Madura culture which has been limited in the academic studies of Madura people. One of the typical cultures of North Madura is a magical ritual culture performance, namely Ojhung Co’ Ghunong. Based on in-depth observations collected by researchers show that Ojhung Co’ Ghunong is the art of fighting between North Madura men as a magical ritual in the tradition of raining during the long dry season. Through the work of the monographic ethnographic method, it was found that the cultural values of life were found among Ojhung Co’ Ghunong. This culture of life is not only an attempt to revitalize drought-stricken agricultural lands, but has also been transformed into educational channels among The North Madurese to maintain their two body strengths, namely material and non-material bodies, in order to become real Madura men.